Preparation of water-dispersible Janus nanosheets from K4Nb6O17·3H2O and their behaviour as a two-dimensional surfactant on air–water and water-toluene interfaces. Issue 9 (11th February 2022) - Suzuki, Ryoko; Nagai, Tomoki; Onitsuka, Emika; Idota, Naokazu; Kunitake, Masashi; Nishimi, Taisei; Sugahara, Yoshiyuki
Abstract : Water dispersible K4 Nb6 O17 ·3H2 O-based Janus nanosheets were successfully prepared and exhibited unique behaviour at the water–air interface and at the water–toluene interface. Abstract : K4 Nb6 O17 ·3H2 O-based Janus nanosheets with water dispersibility and surface activity were prepared via sequential regioselective surface modification. To provide individual Janus nanosheets with these two properties, phenylphosphonic acid and phosphoric acid were utilized for surface modification at interlayers I and II of K4 Nb6 O17 ·3H2 O, respectively, and the resulting product was exfoliated into single-layered nanosheets by ultrasonication in water. The resulting aqueous dispersion of the Janus nanosheets showed lower surface tension than pure water, confirming that the Janus nanosheets had surface activity. An o/w emulsion was formed using the Janus nanosheet aqueous dispersion and toluene. In this emulsion, characteristic phenomena, coalescence and Ostwald ripening behaviour of toluene droplets were observed; the appearance of ellipsoidal droplets during coalescence and a rapid Ostwald ripening which differ from those observed for systems using conventional surfactants, were observed. These phenomena likely originated from the unique anisotropic structures of Janus nanosheets with their nm-scale thickness and μm-range lateral size.